In search of the Kingdom of Loulan - Kikuchi, Harou; Suzuki, Haruo; Tamai, Isao; Tu Guo-bi (The Silk Road, 1990)
Explore the lost kingdom of Lou-lan, which vanished into the sands of the desert. Discover the relics of the Silk Road trade over a millenium ago and the mummy from a grave hidden for more than 2,000 years.